Octreotide in the treatment of neuroendocrine carcinomas: Is the success achieved? - L. Yu. Morgunov (Исследования и практика в медицине, 2015)
Diagnosis and treatment of functioning and non-functioning neuroendocrine tumors is a challenging task. Surgeru remains the only radical method of treatment of these tumors, but tumors often are diagnosed at the stage of metastasis, when only palliative treatment is possible. Octreotide in patients with neuroendocrine tumors remains a drug with proven efficacy that can suppress the clinical symptoms of carcinoid syndrome and has antiproliferative activity, which can improve the quality of life and prolong survival.